2017
DOI: 10.1109/tuffc.2016.2633319
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Study for the Design of an Optimized Ultrasonic Percussive Planetary Drill Tool

Abstract: Abstract-Traditional rotary drilling for planetary rock sampling, in-situ analysis and sample return, is challenging because the axial force and holding torque requirements are not necessarily compatible with lightweight spacecraft architectures in low-gravity environments. This article seeks to optimize an ultrasonic-percussive drill tool to achieve rock penetration with lower reacted force requirements, with a strategic view towards building an Ultrasonic Planetary Core Drill (UPCD) device. The UPCD is a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In previous research [9], the ultrasonic transducer was 0885-3010 (c) 2018 IEEE. Personal use is permitted, but republication/redistribution requires IEEE permission.…”
Section: Ultrasonic Transducersmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research [9], the ultrasonic transducer was 0885-3010 (c) 2018 IEEE. Personal use is permitted, but republication/redistribution requires IEEE permission.…”
Section: Ultrasonic Transducersmentioning
confidence: 99%
“…Previous research [9] on the full wavelength drill tool suggested that a minor change in the mass of the free-mass, within a specified range, will not significantly affect the delivered impulse to the impact plate, and consequently a 6g toroidal free-mass is selected. For the drill-bit, it was found that a similar level of impulse was delivered to the impact plate using one drill-bit or multiple connected drillbits, and therefore a single drill-bit element (80g) is used throughout.…”
Section: Experimental Parametric Study Of the Ultrasonic Percussive Smentioning
confidence: 99%
“…The drill uses the ultrasonic-percussive technique, where the transducer assembly is free to travel as a sprung mass (via front and back springs) over several mm in order to deliver recurring percussive interactions with a free-mass, which then goes on to hammer against the drill string. This concept is covered further in Li, et al, (2017). The travel range is additionally exploited to permit the relative vertical movement needed to connect and disconnect the drillstring elements.…”
Section: Ultrasonic Planetary Core Drill Overviewmentioning
confidence: 99%
“…Generally, a PT can be equivalent to a simple circuit shown consisting of two arms as shown in Fig. 1 [11,12]. The first arm is the electric arm containing a parallel capacitor and a dielectric resistance .…”
Section: Introductionmentioning
confidence: 99%